Pattern of pediatric skin disorders in Murtala Muhammad Specialist Hospital Kano, Nigeria - Yahya, Aishatu (Acta Biomedica Atenei Parmensis, 2020)
Abstract Background:Skin disorders are very common in children. Wide spectrum of skin disorders is seen among children. The spectrum of skin disorders seen in children vary from region to region.Aim of the work:The study is aimed to determine the pattern of skin disorders among children in Pediatric dermatology clinic of Murtala Muhammad Specialist Hospital, Kano, Nigeria.  Methods:It was a descriptive cross-sectional study. Subjects were consecutively recruited. Using a semi-structured questionnaire, demographic history of the subjects and history of skin disorders were obtained from all the subjects and detailed physical examination was carried out with particular emphasis on skin lesion examination after obtaining an informed consent. Ethical clearance was obtained from Ethical committee of the hospital. Data obtained was analyzed using SPSS version 24.Results: A total of 338 subjects were recruited. One hundred and seventy-three (51.2%) were males and 165 (48.8%) were females.There were 35 specific types of skin disorders observed. Infections and infestations were the commonest category of skin disorders seen among 47% of the children followed by inflammatory skin disorders observed among 36.9% of the subjects. Tinea capitis was the commonest type of skin disorder observed among 15.5% of the subjects followed by atopic eczema (13.0%).Tinea capitis was significantly commoner among male children aged 6-10 years (p